Long non-coding RNA AFAP1-AS1 facilitates ovarian cancer progression by regulating the miR-107/PDK4 axis - Bao Liu; Li Yan; Yugang Chi; Yuhan Sun; Xiaoyu Yang (BMC, 2021)
Abstract Background Abnormally expressed in various tumors, long non-coding RNAs (lncRNAs) feature prominently in tumor development, yet little is still known regarding the functional roles of lncRNA AFAP1 antisense RNA 1 (AFAP1-AS1) in ovarian cancer (OC). Methods The relative expression levels of lncRNA AFAP1-AS1, microRNA (miR)-107 and pyruvate dehydrogenase kinase isozyme 4 (PDK4) mRNA were assessed by quantitative real-time PCR. PDK4, PCNA and cyclin D1 expression levels were determined using Western blot analysis. Bioinformatics analysis and dual-luciferase gene reporter assay were conducted for identifying and validating the binding sequences between AFAP1-AS1 and miR-107, as well as between miR-107 and PDK4. Cell counting kit-8 assay was employed for detecting cell proliferation. Cell migration and invasion abilities were examined using Transwell assays. Results The present study revealed that AFAP1-AS1 expression was elevated in OC cells and tissues. AFAP1-AS1 expression and FIGO stage were positively correlated. AFAP1-AS1 knockdown repressed OC cell proliferation, migration and invasion. AFAP1-AS1 functioned as a sponge of miR-107, and miR-107 reversed the effects of AFAP1-AS1 on OC cells. It was validated that miR-107 was able to bind to PDK4, and AFAP1-AS1 regulated PDK4 expression by competitively binding with miR-107. Additionally, miR-107 modulated OC cell proliferation, migration and invasion via targeting PDK4. Conclusions LncRNA AFAP1-AS1 serves as a tumor driver in the pathogenesis of OC via the miR-107/PDK4 axis.